Modifications of Parylene by Microstructures and Selenium Nanoparticles: Evaluation of Bacterial and Mesenchymal Stem Cell Viability - Pekarkova, Jana; Gablech, Imrich; Fialova, Tatiana; Bilek, Ondrej; Fohlerova, Zdenka (Frontiers in Bioengineering and Biotechnology, 2021)
Parylene - based implants or coatings introduce surfaces suffering from bacteria colonization. Here we synthesized polyvinylpyrrolidone stabilized selenium nanoparticles (SeNPs) as the antibacterial agent, and various approaches are studied for their reproducible adsorption and thus modification of parylene C coated glass substrate. The nanoparticle deposition process is optimized in the nanoparticle concentration to obtain evenly distributed NPs on the flat parylene C surface. Moreover, the array of parylene C micropillars is fabricated by plasma etching of parylene C on a silicon wafer, and the surface is modified with SeNPs. All designed surfaces are tested against two bacterial pathogens, Escherichia coli (gram-negative) and Staphylococcus aureus (gram-positive). The results show no antibacterial effect toward S. aureus, while some bacteriostatic effect is observed for E. coli on the flat and microstructured parylene, respectively. However, SeNPs did not enhance the antibacterial effect against both bacteria. Additionally, all designed surfaces show cytotoxic effects toward mesenchymal stem cells at high SeNPs deposition. These results provide valuable information about the potential antibacterial treatment of widely used parylene C in biomedicine.